Determination of parametres of the air-void system in airfield pavement concrete using computed tomography - Kowalska, Danuta; Iwanowski, Paweł; Kowalewska, Agata (International Conference “Environmental Engineering”, 2017)
Immediately after completion airfield pavements begin a gradual deterioration that is attribute to several factors. One of the major elements contribute to airfield pavement deterioration is exposure to the environment (freezing thawing and de-icing salts). Air o ids microstructure in cement-based materials is an important feature related to the freeze haw durability of these materials since all the adverse influences are result of potentially harmful ionic fluids and aggressive gas transport through the concrete and the transport properties strongly depend on the morphology of the pores inside the concrete. For revealing the porous microstructure in airfield pavement concrete X a y tomography method was used. New and advance methodologies have been developed to determine the basic parameters of air entrainment in concrete (total content of the air, specific surface area of the air-voids system, spacing factor and content of micropores) by summing the distances traversed across a given component along a series of regularly spaced lines in one or more planes intersecting the sample. Using the method mentioned above, to meet requirements of PN N 480 1 specification (describes procedure for microscopical determination of air voids characteristics in hardened concrete), the original software was applied – AVCT (Air Void by Computed Tomography) computer programme. The specimens for CT testing were cylinders extracted by drilling out from the investigated concrete core or cubic specimen. The CT method does not require any special processing of the surface of tested specimen as opposed the common method according to PN N 480 1, by which the properly polished section is a prerequisite for obtaining proper results of air voids characterization. The paper presents the results of the evaluation of air o ids microstructure in concrete conducted with the application of computed tomography method. Exemplary images of distribution and size of air o ids in concrete specimens have been presented. Special attention was paid to obtain effective image resolution.
Keywords: cement concrete; air voids; parameters of air entrainment; X-ray CT